Conformational Equilibrium of NADPH–Cytochrome P450 Oxidoreductase Is Essential for Heme Oxygenase Reaction - Sugishima, Masakazu (Antioxidants (Basel), 2020)
Heme oxygenase (HO) catalyzes heme degradation using electrons supplied by NADPH–cytochrome P450 oxidoreductase (CPR). Electrons from NADPH flow first to FAD, then to FMN, and finally to the heme in the redox partner. Previous biophysical analyses suggest the presence of a dynamic equilibrium between the open and the closed forms of CPR. We previously demonstrated that the open-form stabilized CPR (ΔTGEE) is tightly bound to heme–HO-1, whereas the reduction in heme–HO-1 coupled with ΔTGEE is considerably slow because the distance between FAD and FMN in ΔTGEE is inappropriate for electron transfer from FAD to FMN. Here, we characterized the enzymatic activity and the reduction kinetics of HO-1 using the closed-form stabilized CPR (147CC514). Additionally, we analyzed the interaction between 147CC514 and heme–HO-1 by analytical ultracentrifugation. The results indicate that the interaction between 147CC514 and heme–HO-1 is considerably weak, and the enzymatic activity of 147CC514 is markedly weaker than that of CPR. Further, using cryo-electron microscopy, we confirmed that the crystal structure of ΔTGEE in complex with heme–HO-1 is similar to the relatively low-resolution structure of CPR complexed with heme–HO-1 in solution. We conclude that the “open–close” transition of CPR is indispensable for electron transfer from CPR to heme–HO-1.